Slime Attack! A forced collaboration game across four iPads designed for children in primary school - Andreasson, Adam; Djukic Dimander, Viktor; Illipe, Daniel; Olsson, Patrik; Randevik, Marcus; Svensson, Viktor (My University, 2018)
The increased usage of tablets in recent years has caused significant changes throughout society. This change can also be seen in schools where tablets are now incorporated throughout primary education. Though, tablets are often used individually causing a lack of collaboration, which is an essential part of education. This paper describes the development process of the mobile game Slime Attack! and how it encourages young children aged 7-9 to cooperate while playing. Slime Attack! is a castle defence game, played on four iPads placed adjacent to each other, collectively forming a large playing field. Initially, a prestudy was carried through, mainly focusing on interaction design theory. Another important basis came from interviews concluded with the intended user group. The gained knowledge from the prestudy provided a foundation for the development to further build upon. This foundation, summarized in a number of strict requirements, together with the narrow scope of the project were thereafter used to form the final game concept. Slime Attack! was shown to encourage collaboration amongst children by fueling a discussion of strategies concerning the expansion of their outpost, and also in supporting each other when the amount of enemies increased. We also discuss flaws in the prototype, including the children’s initial competitive playing style, and issues with the user interface that slowed down the onset of collaboration. Finally, we put forth a number of possible changes to the game that would address the major flaws we found in our tests.
Keywords: Data- och informationsvetenskap; Computer and Information Science